2003
DOI: 10.1523/jneurosci.23-27-09133.2003
|View full text |Cite
|
Sign up to set email alerts
|

sup-9, sup-10, andunc-93May Encode Components of a Two-Pore K+Channel that Coordinates Muscle Contraction inCaenorhabditis elegans

Abstract: Genetic studies of sup-9, unc-93, and sup-10 strongly suggest that these genes encode components of a multi-subunit protein complex that coordinates muscle contraction in Caenorhabditis elegans. We cloned sup-9 and sup-10 and found that they encode a two-pore K ϩ channel and a novel transmembrane protein, respectively. We also found that UNC-93 and SUP-10 colocalize with SUP-9 within muscle cells, and that UNC-93 is a member of a novel multigene family that is conserved among C. elegans, Drosophila, and humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 55 publications
3
92
0
Order By: Relevance
“…acr-2, unc-5 ) [14,15] (Additional file 14) whereas, a lower threshold of 1.5× included significantly more false positives (e.g. muscle genes, pat-3, sup-10 ) [16,17]. …”
Section: Resultsmentioning
confidence: 99%
“…acr-2, unc-5 ) [14,15] (Additional file 14) whereas, a lower threshold of 1.5× included significantly more false positives (e.g. muscle genes, pat-3, sup-10 ) [16,17]. …”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis was further corroborated by the finding that a reduction in the general excitability of body wall muscle cells can also reduce polyQ aggregation. Specifically, we observed that a gain-of-function mutation in unc-93, a gene encoding a subunit of the K + channel complex that is known to reduce muscle contraction (de la Cruz et al 2003), decreased polyQ aggregation in body wall muscle cells (Supplementary Fig. S4B).…”
Section: Cholinergic Hyperstimulation Causes Premature Polyq Aggregatmentioning
confidence: 98%
“…5; Supplementary Movie Fig. S3) encoding an evolutionarily conserved component of a two-pore potassium channel complex and known to be critically required for muscle contraction in Caenorhabditis elegans (de la Cruz et al 2003). The Drosophila CG8698 gene is specifically expressed in differentiating somatic muscles starting from stage 14, and its transcripts are particularly abundant in late embryonic stages in functional, contracting muscles (Fig.…”
Section: Functional Properties Of Muscle and Heart Cells Are Controllmentioning
confidence: 99%